2019
DOI: 10.32852/iqjfmme.v20i3.512
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of New Design of Solar Water Distillation Coupled With Flat Plate Solar Water Collector

Abstract: An experimental investigation involves the effect of the turning hollow-cylinder within a solar water distillation on the output of distillate water. This study is to be conducted in order to validate the optimum productivity of purification water by turning hollow-cylinder. The experiments were carried out in Kirkuk city, Iraq, 2018.Experimental results demonstrated that a basin water height is (1 cm) gives the better productivity of (1225 ml/ m2.day) for the conventional solar water distillation, and (2 cm) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…The cumulative distillate water output from the modified solar still increased compared with the conventional solar still by a factor not less than 240%. [17] this study is to be conducted to validate the optimum productivity of purification water by turning hollow-cylinder. Experimental results demonstrated that a basin water height is (1 cm) gives better productivity of (1225 ml/ m2.day) for conventional solar water distillation, and (2 cm) basin water height for the modification solar water distillation gives the optimum productivity, which is (3540 ml/m2.day) which represent an increase of 188% when compared with the productivity of the conventional solar water distillation.…”
Section: Solar Energy Technologiesmentioning
confidence: 99%
“…The cumulative distillate water output from the modified solar still increased compared with the conventional solar still by a factor not less than 240%. [17] this study is to be conducted to validate the optimum productivity of purification water by turning hollow-cylinder. Experimental results demonstrated that a basin water height is (1 cm) gives better productivity of (1225 ml/ m2.day) for conventional solar water distillation, and (2 cm) basin water height for the modification solar water distillation gives the optimum productivity, which is (3540 ml/m2.day) which represent an increase of 188% when compared with the productivity of the conventional solar water distillation.…”
Section: Solar Energy Technologiesmentioning
confidence: 99%
“…The globe is grappling with a scarcity of water owing to industrialization, population growth, and water contamination; hence, it is imperative to investigate alternative decentralized systems like passive solar distillers that rely on renewable sources of energy to cater to the requirements of rural regions, even though their manufacture is somewhat constrained [4]. Clean drinking water may be distilled from dirty sources using solar energy, a sustainable and inexpensive power source that does not contribute to greenhouse gas emissions via the process of solar water distillation [5].…”
Section: Introductionmentioning
confidence: 99%
“…Notable examples include coal, oil, and natural gas. Conversely, renewable energy, inherently replenished by nature, offer cleaner alternatives devoid of harmful pollutants [1]. Makhzom et al based their research on actual measured data collected over long periods by the monitoring and control systems of the power plants in question.…”
Section: Introductionmentioning
confidence: 99%